Beyond Scores: Using Converging Evidence to Determine Speech and Language Services Eligibility for Dual Language Learners - Castilla-Earls, Anny; Bedore, Lisa; Rojas, Raúl; Fabiano-Smith, Leah; Pruitt-Lord, Sonja; Restrepo, María Adelaida; Peña, Elizabeth (American journal of speech-language pathology, 2020)
Purpose Speech-language pathologists have both a professional and ethical responsibility to provide culturally competent services to dual language learners (DLLs). In this tutorial, we recommend that clinicians use a comprehensive assessment of converging evidence to make diagnostic decisions in DLLs in accordance with the American Speech-Language-Hearing Association's Code of Ethics. The content of this tutorial is most appropriate for Spanish-English DLLs between the ages of 4 and 8 years. Method We propose a converging evidence approach, in which one single method is not the deciding factor in making diagnostic decisions regarding the dual language and speech production skills of DLLs. Converging evidence refers to the idea that multiple pieces of assessment data must come together and trend in the same direction to make a diagnostic decision. We recommend gathering assessment data using a combination of language experience questionnaires, bilingual language sample analysis using large-scale reference databases, evaluation of learning potential, and standardized testing. These four assessment methods allow clinicians to examine the child in different contexts to determine their strengths and weakness in communication abilities. Conclusion We illustrate the converging evidence framework using two case studies to guide the clinician through the diagnostic decision-making process.